ANALISIS HUBUNGAN SIKAP DAN MOTIVASI TERHADAP PRESTASI BELAJAR BAHASA BALI MAHASISWA BARU JURUSAN PENDIDIKAN BAHASA BALI TAHUN AJARAN 2013-2014 (Studi Psikometrik dalam Rangka Rekrutmen Mahasiswa Baru Jur. Pendidikan Bahasa Bali) - I Nengah Martha; Sang Ayu Putu Sriasih; Made Sri Indriani (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2013)
This investigation aims to reveal the main problems: 1) Is there any relationship between the attitude and the Balinese learning achievement of the new university students at the Balinese education department? 2) Is there any relationship between the motivation and the Balinese learning achievement of the new university students at the Balinese education department? 3) ) Is there any influence the attitude towards the Balinese learning achievement of the new university students at the Balinese education department? 4) ) Is there any influence the motivation towards the Balinese learning achievement of the new university students at the Balinese education department? 5) Are there any influence the attitude and motivation towards the Balinese learning achievement of the new university students at the Balinese education department? 6) Is where have more influence towards the Balinese learning achievement of the new university students at the Balinese education department, their attitude or their motivation? 7) Is where musch be given more attention for improving the Balinese learning achievement of the new university students at the Balinese education department, their attitude or their motivation? This investigation was held at Undiksha in 2013/2014. The data of investigation were analized quantitatively by statistical analysis, namely: 1) simple correlation analysis, 2) linear regression analysis one predictor, 2) linear regression analysis two predictor. Finally, this investigation resulted the following findings: 1) There is a significant correlation between the attitude and the Balinese learning achievement of the new university students at the Balinese education department. 2) There is a significant correlation between the motivation and the Balinese learning achievement of the new university students at the Balinese education department. 3) ) There is a significant influence the attitude towards the Balinese learning achievement of the new university students at the Balinese education department. 4) There is a significant influence the motivation towards the Balinese learning achievement of the new university students at the Balinese education department. 5) There are a significant influence the attitude and motivation towards the Balinese learning achievement of the new university students at the Balinese education department? 6) Motivation have more influence towards the Balinese learning achievement of the new university students at the Balinese education department. 7) There for, the motivation musch be given more attention for improving the Balinese learning achievement of the new university students at the Balinese education department. The conclution, the attitude and motivation have an influence towards the Balinese learning achievement. Suggested that, their attitude and motivation need to considerated on selection of a new university student at the Balinese education department – Undiksha.Key words: correlation, attitude and motivation, learning achievement